Decision Support System (DSS) of Project Delay for Improving Project Performance in Construction Project - Faizal, Nurul Firzanah; Kasim, Narimah; Ang, Peniel Ang Soon Ern; Ismail, Zul-Atfi; Namara, Idi (Journal of Technology Management and Business, 2025)
Malaysia’s construction industry continues to play a significant role in the country’s economy and facing problems such as material shortages, quality control, payment disputes, communication breakdowns, and delays in making decisions. Project performance is always affected by project delays due to ineffectively managed construction projects. Thus, this research aims to provide a mechanism for project delay decision support for improving project performance in construction projects. Therefore, the research objectives are to identify the critical factors of project delay affecting the improvement of project performance and analyses decision support requirements in mitigating project delays. Furthermore, a decision support system for mitigating project delays to improve project performance in construction projects will be developed. This research used a qualitative approach for primary data collection with semi-structured interview questions used for data collection. Respondents from G7 Contractors located at Selangor and Wilayah Persekutuan Kuala Lumpur were involved in this research. Data collection from respondent’s feedback was analysed through content analysis. Significant findings from this research identified the critical factors of project delay: material shortages, quality control, payment disputes, communication breakdowns, and delays in making decisions. Additionally, human, financial, and materials were significantly identified for decision support requirements. Google Slides and Google Spreadsheets were used for decision support system development and the system has undergone the testing for system application. In conclusion, this research enables us to comprehend the application of a decision support system during the decision-making process to minimize project delays.